Understanding the synergistic effects of cobalt single atoms and small nanoparticles: enhancing oxygen reduction reaction catalytic activity and stability for zinc-air batteries - Wang, Zhe (2022)
The development of earth-abundant oxygen reduction reaction (ORR) catalysts with high catalytic activity and good stability for practical metal-air batteries remains an enormous challenge. Herein, a highly efficient and durable ORR catalyst is reported, which consists of atomically dispersed Co single atoms (Co-SAs) in the form of Co-N4 moieties and small Co nanoparticles (Co-SNPs) co-anchored on nitrogen-doped porous carbon nanocage (Co-SAs/SNPs@NC). Benefiting from the synergistic effect of Co-SAs and Co-SNPs as well as the enhanced anticorrosion capability of the carbon matrix brought by its improved graphitization degree, the resultant Co-SAs/SNPs@NC catalyst exhibits outstanding ORR activity and remarkable stability in alkaline media, outperforming Co-SAs-based catalyst (Co-SAs@NC), and benchmark Pt/C catalyst. Density functional theory calculations reveal that the strong interaction between Co-SNPs and Co-N4 sites can increase the valence state of the active Co atoms in Co-SAs/SNPs@NC and moderate the adsorption free energy of ORR intermediates, thus facilitating the reduction of O2. Moreover, the practical zinc-air battery assembled with Co-SAs/SNPs@NC catalyst demonstrates a maximum power density of 223.5 mW cm–2, a high specific capacity of 742 W h kg–1 at 50 mA cm–2 and a superior cycling stability.